Pengaruh Kualitas Pelayanan Dan Kepuasan Kerja Terhadap Kinerja Pegawai Di Balai Diklat Keagamaan Kota Palembang - Pebrian , Rahmad Ab; Syarifudin , Achmad; Pohan , Hasril Atieq (Jurnal Ilmu Sosial, Humaniora dan Seni, 2023)
This thesis is entitled "The Influence of Service Quality and Job Satisfaction on Employee Performance at the Palembang City Religious Training Center." Relatively good job satisfaction seems to contribute to employee performance to keep working better and to show high performance to provide responsibility in supporting the welfare and success of the company. The object of research is the employees of the Palembang City Religious Education and Training Center totaling 86 employees. The research objective was to determine the effect of service quality on performance, the effect of job satisfaction on performance, and the effect of service quality on employee performance at the Palembang City Religious Education and Training Center. This type of research is quantitative research. Based on the analysis that has been done, the effect of service quality is proven through multiple linear tests, namely the significance value of the X1 variable quality of 0.001 <0.05 means that there is a significant and positive influence between service quality on employee performance. The influence of job satisfaction, namely the regression coefficient value of satisfaction is 0.511, meaning that if the satisfaction variable (X2) and constant (a) is 0 (zero), then employee performance (Y) increases by 0.511. The influence of Service Quality and Job Satisfaction, namely by means of the t test (hypothesis) absolutely proves the results of the acquisition show that the value of tcount is 6,690 > 1,886, it can be concluded that Ha is accepted and Ho is rejected, to see significant results it is known that the value of multiple linear sig = 0.000 <0.05 it is stated significance. So it can be concluded that there is a significant influence on service quality, satisfaction on the performance of Palembang City Education and Training Center employees with a category of 94.3% showing very strong results where the achievement of targets for performance issues and employee satisfaction has reached a maximum value of more than 90%.